How to measure barriers in accessing mental healthcare? Psychometric evaluation of a screening tool in parents of children with intellectual and developmental disabilities - Ting Xiong; Elisa Kaltenbach; Igor Yakovenko; Jeanine Lebsack; Patrick J. McGrath (BMC, 2022)
Abstract Caring for children with intellectual and developmental disabilities (IDD) can cause an enormous physical and emotional burden, and therefore these parents have an elevated risk to experience mental health problems. The characteristics of current healthcare systems and parents' responsibilities to care for their children seem to impede their access to mental healthcare. There is so far a lack of instruments to screen for such obstacles. The aim of this study was to develop and validate a scale for measuring barriers to accessing mental healthcare. The Parental Healthcare Barriers Scale (PHBS) was developed on the basis of an extensive literature research, input and discussion from experts and parents with lived experience. A cross-sectional survey was used to collect data from 456 parents of children with IDD. Physical health, mental health, social support, and parenting were measured for concurrent and discriminant validity of the PHBS. The PHBS scale revealed acceptable to good reliability and validity. It consists of four subscales (i.e., support accessibility, personal belief, emotional readiness, and resource availability). The PHBS found parents prioritized their children's treatments over their own mental health challenges (93.4%), did not have enough time (90.4%), and had financial concerns (85.8%). Parents in rural and remote areas had more limited resources. Findings from our study suggest increasing financial support for the parents seeking mental health services, introducing evidence-based treatments, increasing the availability of healthcare services for parents, and adjusting current services to their needs.